Application of paper sludge ash and incinerated sewage ash in emulsified asphalt cold mixtures - Dulaimi, Anmar; Qaidi, Shaker; Al-Busaltan, Shakir; Milad, Abdalrhman; Sadique, Monower; Kadhim, Mustafa Amoori; Al-Khafaji, Ruqayah; Sabri Sabri, Mohanad Muayad (Frontiers in Materials, 2023)
Certain disadvantages could have appeared while using hot mix asphalt (HMA), such as the release of unhealthy gases into the environment (environmental issues), difficulty in sustaining the temperature over long distances (logistical issues), and consuming a sufficient amount of energy while preparing and laying down (practical and economic issues). To overcome the aforementioned issues, this study aimed to develop rapid-curing emulsified asphalt cold mixes (EACM) comprising a cementitious filler made from industrial by-product materials. Paper sludge ash (PSA) is used as an active filler for application in the EACM rather than conventional mineral filler. Additionally, to maximize the effect of PSA's hydraulic activity, incinerated sewage ash (ISA) is utilized as an activator at a concentration of 0-4% by mass of the aggregates. The results demonstrate that the use of waste PSA significantly improves the indirect tensile stiffness modulus (ITSM) by around 10 times more after 2 days than the traditional emulsified asphalt cold mixes. In addition, the improvement in ITSM was around 30% and 65% for 6%PSA+1%ISA and 6%PSA+4%ISA mixes, respectively. Furthermore, the rutting for the 6%PSA+1%ISA and 6%PSA+4%ISA mixes decreased to around 19% and 11% in comparison to the traditional 131-pen HMA. The formation of hydration products and rapid demulsification of asphalt emulsion, which results in binding within the mixtures, are responsible for the increased ITSM and rutting resistance. As a result, environmental issues are minimized, and energy preservation may be maintained.